PENERAPAN PEMBELAJARAN TEMATIK-EKSPLORATIF-DEMOKRATIK (TED) DALAM BELAJAR FISIKA DI ALAM TERHADAP KEMAMPUAN KOGNITIF MAHASISWA - Tumangkeng, Jeane Vera; Lahope, Kenny Setiawan (Charm Sains: Jurnal Pendidikan Fisika, 2024)
TED Learning Strategy (Thematic-Explorative-Democratic) about nature activity in tumimperas waterfall is an example of physics learning process by utilizing the surrounding nature as an object in learning. The purpose of this study was to determine the application of TED learning strategies in learning physics in nature to improve cognitive abilities. The method used in this research is Experimental research (True Experiment) with the design used Posttest-Only Control Design. This research was conducted through two stages. The first stage is to give treatment (treatment) the application of the TED learning strategy and the second stage is to give a posttest as an evaluation of learning. The samples in the study were students of Physics Education Study Program of Universitas Negeri Manado where the samples were taken randomly and divided into two classes. After obtaining the data, the research results were processed statistically with the help of IBM SPSS Statistics 22 for windows. Based on the results of statistical analysis, it shows that student learning outcomes come from a normally distributed population, are homogeneous and the results of the calculation of the t-test hypothesis reject H_0 and accept H_1. so it can be concluded that there is a significant difference between the physics learning outcomes of students taught by using the TED learning strategy with students taught by not using the TED learning strategy.